Surgical management of fibrous dysplasia-related lip paresthesia: A case report - Elver Atalay; Bedriye Gizem Çelebioğlu Genç (Balkan Stomatological Society, 2024)
This study aims to describe a case of fibrous dysplasia causing lip paresthesia and the surgical treatment applied, highlighting the roles of dentists and oral and maxillofacial surgeons in managing such cases. Case Report: A 37-year-old female presented with right-sided lip paresthesia. Diagnostic imaging, including panoramic radiography and Cone Beam Computed Tomography (CBCT), was used to assess the lesion. The patient underwent surgery under general anesthesia. After local anesthesia, an incision was made, the periosteum was elevated, and the expanded bone was exposed. The buccal cortical bone was removed, and the radiopaque lesion was enucleated, exposing the mandibular nerve. The excised tissue was sent for pathological examination. Postoperative care included antibiotics, painkillers, and mouthwash, with detailed wound care instructions. A follow-up visit was conducted one year post-surgery. Panoramic radiograph and CBCT revealed a radiopaque lesion above the mandibular canal with a radiolucent halo. The lesion was successfully enucleated, exposing the mandibular nerve without further damage. Histopathology confirmed fibrous dysplasia. One year post-surgery, the patient had no recurrence of paresthesia or lesion regrowth, although a slight radiolucent area remained visible on the panoramic x-ray. Conclusions: Fibrous dysplasia is a rare, benign bone disorder requiring comprehensive diagnostic evaluation and careful management. In this case, surgical excision was necessary due to the lesion's impact on the mandibular canal and resulting lip paresthesia. The successful outcome highlights the importance of early diagnosis, interdisciplinary collaboration, and long-term follow-up.